The Influence of Digital Green Marketing and Applications in Increasing Customer Loyalty - Palupi, Catur; Satoto, Eko Budi; Supeni, Retno Endah (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to analyze the influence of digital green marketing and ease of application on customer loyalty of BRImo users. The research sample consisted of 100 respondents using BRImo who were selected by purposive sampling. Using a quantitative approach and multiple linear regression analysis, this study examines how digitally communicated eco-friendly marketing strategies and the ease of use of the BRImo application contribute to building customer loyalty. The results of the study show that these two variables have a significant effect on customer loyalty. Digital green marketing increases customer awareness and trust in Bank BRI’s commitment to environmental sustainability, while the ease of application, including intuitive navigation, transaction speed, complete features, and security, increases user comfort and satisfaction. These findings affirm the importance of integrating sustainability and user experience aspects in the development of digital banking services to maintain customer loyalty in the digital era. This research provides recommendations for Bank BRI to continue to optimize application features and strengthen digital green marketing campaigns to increase customer loyalty in a sustainable manner.